Efektivitas Ibadah Online Bagi Pertumbuhan Rohani Jemaat di Gereja Bethel Indonesia Parakletos Cengkareng - Djone Georges Nicolas; Timothy Amien Rk; Soneta Sang Surya Siahaan; Weni Lolinga; Sedirman Lalowo (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aimed to examine the effectiveness of online worship for the spiritual growth of the Bethel Church of Indonesia Parakletos Cengkareng, using a descriptive qualitative method approach and data collection through the Bible and various books and journals and interviews. Online worship at the beginning of the Covid-19 pandemic was considered ineffective by several individuals, including pastors and congregations, in supporting the spiritual growth of God's community because the distance was considered contrary to the nature of God's assembly as a church, which was called to fellowship in the temple of God in unity. As a result, online worship allows almost all congregations to be involved in every worship activity organized by the church, namely: Raya Worship, Cell Community Worship, Youth and Youth Worship, evening prayer service, worship, Women's worship, Men's worship, fasting worship, and Discipleship worship so that their spiritual growth is increasingly visible through a lifestyle of loving one another